The Effect of Chemical Disinfectants on the Setting Time and Dimensional Change of Alginate Impression Material. - Luma M. Al-Nema (University of Mosul, College of Dentistry, 2018)
Abstract Aims: The aim of this study was to evaluate the effect of mixing different concentrations of chlorhexidine, iodine ,and sodium hypochlorite solutions on the setting time and dimensional change of alginate impression material. Materials and methods: Total number of samples (40) has been prepared in this study. Ten samples for control group made from pouring alginate impressions of metal model .The other groups made by mixing alginate with 0.05% iodine, 0.5% chlorhexidine and 0.5% sodium hypochlorite solutions. Dimensional change was measured with AutoCAD program .The Setting time was also measured for each group. Statistical analysis was performed using ANOVA and Duncan multiple range test. Results: no significant difference in the linear dimensional change among the tested groups ,sodium hypochlorite added to alginate as disinfectant showed the highest dimensional changes among the other groups. There was a significant difference among the tested groups in the setting time. It was found that treating the alginate with sodium hypochlorite and chlorhexidine disinfecting agents accelerated the setting time of the material. Conclusion: The testing disinfecting agents can be used safely regarding dimensional change.